A leitura como instrumento de desenvolvimento do aluno leitor: uma proposta de atividades em uma turma de 8º ano em uma escola de Mosqueiro - PORTELA, Sâmela Aires dos Santos (Universidade Federal do Pará, 2017)
This work was made from a supposing that the Reading is one of the paths which the student develop knowledge and it´s one of the tools for a critical construction´s human being, somebody who uses his/her speakings and able to interact in an efficient way with his/her surrounding people. In this context, we discuss about a school ´s need , it has to lead a role play not only in the reader´s formation, but as well as a space to the development from the reader´s student. From this language interracionalist´s conception, mainly based in Bakhtin and Menegassi, we discuss this necessity and we ask, from a previously approach with a eighth year classroom from the elementary school from Mosqueiro, what can be done so that the student show a development and reading autonomy ? Trying to answer this question which bother us, we had to identify an objective, from some activities perspective, some advances in the reader´s development from the students, so that it could become an expert reader and able to evolve in the most several communicative intereactions. From this signal given by the students in this previous activity, we can verify that the classroom had some difficulties since their understanding´s level until the reading retention´s level . Through this, we proposed a work with reading´s activities, focused in the decodification´s levels, understanding, interpretation and retention, until to arrive at activities culminating with the Touristic reports´gender. From this result on , we noticed some advances in their reading from the third activity on, when we started reading´s strategies, such as resumes´production, presented by Solé (1998). In the later activities, we verified that the students were increasing their knowledge and improving their development in the steps from this reading process. Finally, we testified, that the most of the students, an appropriation from reading steps, when the readers- students made some interviews and they got, from these interviews, retextualize to the Touristic reports´gender applying, indeed, some strategies such as those learned at resume´s work, informations´selection made, besides their criticism´s display revealed during this process, that it finished with a touristic reportmagazine´s production.